Engineering and characterization of materials inspired by the Humboldt Squid sucker ring teeth - Ho, Chin Guan (2015)
Hydrogel has the ability to encapsulate bioactive molecules and hence become attractive choice as scaffolding materials. Short and ultrashort peptides derived from suckerin protein of Humboldt squid (Dosidicus Gigas) were integrated into hydrogels and studied. A few methods have been tried in this study to achieve hydrogel formation, however due to the short peptide sequences and its properties, the peptides could not self-assemble into gels with the tested methods. By using a Chitosan scaffold, the short peptides could be successfully integrated into a gel. Five techniques were applied to characterize the peptide hydrogels: swelling test, rheometer, SEM, DSC and FTIR. The peptide-chitosan hydrogels exhibited high water absorption and retention ability, and highly porous network structures were observed through SEM. High value of free water state obtained by DSC contributed to high peptide content in hydrogel. Moreover, a high percentage of β-sheet was observed via deconvolution of obtained FTIR spectra, which is postulated to correlate to the high stiffness values (1 to 10kPa) obtained by rheological experiments. Through these characterization techniques, it showed that peptide could be integrated into a hydrogel and play a role in tailoring the mechanical, physical and chemical properties of the gel.